2022
DOI: 10.1159/000520648
|View full text |Cite
|
Sign up to set email alerts
|

Hematohidrosis, Hemolacria, and “Trichorrhage”: A Systematic Review

Abstract: <b><i>Introduction:</i></b> Hematohidrosis and hemolacria are 2 conditions surrounded in religiousness, mysticism, and supernatural superstitions. While the mechanism is still unclear, these cases have amazed physicians for centuries. <b><i>Methods:</i></b> We performed a systematic review in PubMed from 2000 to mid-2021 accounting for 75 studies from which we included 60 cases in 53 articles which were described. <b><i>Results:</i></b> Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Genetic mutations related to ECM function and development can affect vessel integrity and formation and can lead to a bleeding phenotype. 5 Cases 37 and 38 are siblings, suggesting potential familial association in patients who experience hematohidrosis. The mother of cases 37 and 38 is reported to have a sibling who passed away due to some unknown bleeding complication, potentially additionally suggestive of familial association in cases of hematohidrosis.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic mutations related to ECM function and development can affect vessel integrity and formation and can lead to a bleeding phenotype. 5 Cases 37 and 38 are siblings, suggesting potential familial association in patients who experience hematohidrosis. The mother of cases 37 and 38 is reported to have a sibling who passed away due to some unknown bleeding complication, potentially additionally suggestive of familial association in cases of hematohidrosis.…”
Section: Letter To the Editormentioning
confidence: 99%
“…2 There seems to be increasing literature on hematohidrosis (given the tempo of case reports published) as noted by Duffin, 3 when comparing articles published between 1880 and 1935, and 1952 and 2016. As compared with 76 cases analyzed by Holoubek and Holoubek in 1996 (many of which were from before the 20th century) 4 and 25 cases by Kluger 2 in 2017 and 28 peer-reviewed cases by Duffin 3 in 2017, Carrion-Alvarez et al 5 identified 60 cases; however, this review included cases of trichorrhage (bleeding from hair follicles) and hemolacria. This could be attributed to a true increase in incidence of the condition, or an increase in the recognition or reporting of such cases.…”
Section: Tablementioning
confidence: 99%
“…Only 23 paediatric cases of idiopathic haemolacria have been reported in the literature. 6 It may be associated with haematidrosis, epistaxis, haematemesis and bloody otorrhoea. 7 One case of vaginal bleeding was reported in a 9-year-old girl.…”
Section: A Young Girl Crying Out Blood: Haemolacriamentioning
confidence: 99%
“…It has been historically linked to mysticism and spirituality. 1 Its incidence and prevalence are unknown, but a recently published study by Shafique et al 2 found 36 cases reported since 1952, mainly pediatric patients (83%) with a mean age of 11 years and female predominance.…”
mentioning
confidence: 99%
“…However, its clinical relevance is not clear yet. 1 This is a diagnosis of exclusion. It is essential to witness the episodes and rule out disorders associated with vascular fragility (i.e., vasculitis and connective tissue disorders), factitious disorders, and chromhidrosis.…”
mentioning
confidence: 99%